Family life under strain: the impact of forced migration on refugee parenting in reception centers - Drummond Johansen, Jennifer; Varvin, Sverre; Sagbakken, Mette (Frontiers in Psychology, 2025)
IntroductionThe global refugee crisis has reached unprecedented levels, with millions, including a significant number of children, being displaced from their homes. Refugees face mental health challenges due to pre-migration trauma, adverse flight experiences, and post-migration stressors which severely impact family dynamics and parenting practices. This study explores the effects of forced migration on refugee parents living in Norwegian reception centers, focusing on how the context of the reception centers influence parenting capacities.MethodsThe research adopts ecological and sociocultural perspectives to understand resilience and parenting within the context of forced migration. Data collection includes individual interviews with 12 parents, field notes, and reflexive accounts, analyzed using Interpretative Phenomenological Analysis (IPA) to capture the participants’ lived experiences.ResultsFindings indicate that the constraints imposed by the asylum system significantly hinder parents’ access to essential resources, leading to increased stress and reduced parenting capacities. Parents reported feelings of being trapped in a state of uncertainty due to a lack of stability and structure. This exacerbated their mental health issues and impaired their ability to provide a secure and nurturing environment for their children. Many parents expressed feelings of isolation and powerlessness.DiscussionThe study highlights the need for host societies to address systemic barriers and provide comprehensive support to refugee families. Interventions should focus on creating a “safe haven” that facilitates psychosocial rehabilitation and supports the well-being of both parents and children. Understanding the broader socio-political context and its impact on refugee parenting practices is crucial and requires shifting from a deficit model of parenting to one that recognizes the resilience and strengths of refugee parents.ConclusionThis research offers a deeper understanding of the complex challenges faced by refugee parents in reception centers. It underscores the necessity for tailored interventions that address both individual and systemic factors to foster resilience of refugee families. Further studies are essential to explore the long-term effects of forced migration on parent–child relationships and child development, and to develop interventions that support the unique needs of refugee families in various contexts.